Retrospective Study of Transjugular Intrahepatic Portosystemic Shunt Placement for Cirrhotic Portal Hypertension - Santos, Sara (2020)
Background and Aims: Transjugular intrahepatic portosystemic shunt (TIPS) is used for decompressing clinically significant portal hypertension. The aims of this study were to evaluate clinical outcomes and adverse events associated with this procedure. Methods: Retrospective single-center study including 78 patients submitted to TIPS placement between January 2015 and November 2018. Follow-up data were missing in 27 patients, and finally 51 patients were included in the study sample. Data collected from individual registries included demographics, comorbidities, laboratory results, complications, and clinical results according to the indication. Results: Averagepre-TIPS portosystemic pressure gradient decreased from 18.1 ± 5 to 6 ± 3 mm Hg after TIPS placement. Indications for TIPS were refractory ascites (63%, n = 49), recurrent or uncontrolled variceal bleeding (36%, n = 28), and Budd-Chiari syndrome (1.3%, n = 1). TIPS-related adverse events occurred in 29/51 (56.8%) patients, with hepatic encephalopathy (HE) in 21 (41%) patients, sepsis in 3, liver failure in 2, hemolytic anemia in 1, acute pulmonary edema in 1, and capsular perforation in 1 patient. Mean follow-up was 15.7 ± 15 months. First-month mortality was 11.7% (n = 6) (sepsis, n = 3; acute liver failure, n = 2; and recurrence of variceal bleeding, n = 1) and was significantly higher for patients with Child-Pugh >9 points (p = 0.01), model of end-stage liver disease (MELD) scores >19 (p = 0.02), and for patients with a history of HE before the procedure (p = 0.001). Older age (p = 0.006) and higher levels of creatinine (p = 0.008) were significantly higher in patients developing HE after TIPS. Ascites persisted in 21.2% (7/33 patients) and was more frequent in patients with lower baseline albumin levels (p = 0.003). Recurrent variceal bleeding occurred in 22% (n = 4/18 patients) and was more frequent in patients with lower baseline hemoglobin levels (p = 0.03). Conclusion: TIPS is effective in up to 80% of patients presenting with variceal bleeding or refractory ascites. Careful patient selection based on age and HE history may reduce adverse events after TIPS.